Stakeholders or Shareholders? Board members’ personal values and corporate identity - Barbero, Edson Ricardo; Marchiano, Marcello (Review of Business Management, 2016)
Purpose – This article diagnoses the relationship between the value priorities of board members in Brazil and their companies’ identities trending towards stakeholders or shareholders. The paper tested five hypotheses referring to the fact that board members of profitoriented companies are more individualistic, while board members of stakeholder-oriented companies tend to be more collectivist. Design/methodology/approach – A survey was carried out through the Schwartz (1992) values inventory with 74 board members in Brazil. The Brazilian Corporate Sustainability Index (ISE) was considered a proxy for stakeholder orientation. The Mann-Whitney test was used in order to verify if the two independent samples were drawn from populations with equal averages. Findings – In partial consonance with previous research, the board members of stakeholder-oriented companies – those participating in the Corporate Sustainability Index – held less individualistic values. However, for individualistic motivational types, only Stimulation and Hedonism were more frequent in companies not participating in the ISE index. Originality/value – This result amplifies the predictive power of individual values and complements the work of Adams, Licht and Sagiv (2011), which experimentally studied the same relationship within individual choices and in a controlled situation. This article enhances the theory by incorporating the organizational level into the debate. The results suggest that other factors also influence pro-shareholder or pro-stakeholder corporate orientation.